Lateral column lengthening: A cadaveric biomechanical study - Zhu, Mingjie; Ali, Moustafa; H Baldini, Todd; Keeter, Carson; S Myerson, Mark; Li, Shuyuan (Journal of the Foot & Ankle, 2026)
Objective: This cadaveric biomechanical study aimed to investigate the potential cause of the subtalar joint impingement after lateral column lengthening (LCL). Methods: Eight fresh-frozen cadaveric feet underwent sequential LCL osteotomy with grafts of 6 mm, 8 mm, 10 mm, and 12 mm. Uniplanar motion analysis tracked anterior and posterior fragment movements. Mixed linear regression was used to assess correlations between graft size and fragment displacement. Results: During LCL, the anterior fragment shifted anteriorly while the posterior fragment shifted posteriorly, with the anterior shift being greater than the posterior shift. From 6 mm to 12 mm of lengthening, the amount of posterior shift per millimeter peaked at 8 mm of lengthening and then decreased. A linear regression relationship was detected between the amount of lengthening and the anterior shift, with 1 mm lengthening inducing 1.07 mm anterior shift (p < 0.001). Conclusion: In non-deformed cadaveric feet, LCL not only produced an anterior shift as expected but also induced a posterior shift of the tuberosity. Linear correlation was detected between the size of the lengthening and the anterior shift of the anterior fragment. The posterior shift eventually decreased after the insertion of a large graft (10 mm and 12 mm). The clinical application of these findings to flatfoot deformities remains uncertain and should be validated in future studies. Level of Evidence III.